Periodic health evaluation in para athletes: a position statement based on expert consensus - Silva, A.; Pinheiro, L.; Verhagen, E.; Ocarino, J.; Fagher, K.; Ahmed, O.; Dalton, K.; Mann, D.; Weiler, R.; Okoth, C.; Blauwet, C.; Lexell, J.; et al. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Para athletes present a broad range of sports-related injuries and illnesses, frequently encountering barriers when accessing healthcare services1. Furthermore, their diverse impairments and the specialized equipment used in competitions require individualized approaches to comprehend their overall health2. The Periodic Health Evaluation (PHE) is a valuable tool for continuously monitoring athletes` health, screening for health conditions, and identifying barriers to athlete`s performance3. Additionally, the PHE assists in the surveillance of health problems by establishing baseline information for each athlete and providing crucial information in case of emergencies. This position statement aims to guide sports healthcare providers in the PHE for para athletes across key impairment categories: intellectual, musculoskeletal, neurological and vision. METHODS: A panel of sixteen international experts, including epidemiologists, physiotherapists, optometrists, and physicians with expertise in para athlete health, convened via videoconferences to discuss the position statement`s purpose, methods, and themes. They formed working groups to address underlying medical condition, cardiorespiratory, neuromusculoskeletal, nutritional status, mental and sleep health, concussion, and female para athlete health assessment considerations. The PHE`s effectiveness lies in its comprehensive approach. RESULTS: Health history review can provide insights into factors impacting para athlete health, inform physical assessments, and help healthcare providers understand each athlete`s needs. During the PHE, considerations should encompass the specific requirements of the sport modality and the impairment itself. The evaluation enable early interventions tailored to the athletes health history. Moreover, the PHE serves as an opportunity to educate para athletes on preventive strategies that can be integrated into their training routines, enhancing their performance and overall health. CONCLUSION: This position statement can potentially enhance clinical practice and improve the healthcare quality for para athletes, ultimately contributing to their overall health and well-being.